The interrelationship between students’ choice of coping strategy, types of problems, and demographic factors: An exploratory study - Azizy, Afrizal Hasbi; Putri, Adelia Khrisna (Jurnal Psikologi, 2024)
Background: The choice of coping strategies by individuals is influenced by a range of internal and external factors. However, there is limited research on how different types of problems affect these preferences. Purpose: We aim to fill this gap by examining the interplay between coping strategies, problem types, and demographic factors. Method: Using a mixed-method approach, we analyzed secondary data from a survey of Indonesian university students. We analyzed 349 valid responses through three analytical methods. Content analysis was used to identify students' coping methods and the types of problems they faced. We then employed contingency tables and logistic regression to explore the associations among these variables.Findings: We found that high-income students are less likely to experience academic and social problems and more likely to use professional mental health services, that academic problems are linked to active and spiritual coping strategies, that female students are more likely to experience stress regulation problems, and that older students are less likely to employ emotion-regulation strategies. Implication: How students cope with their problems are influenced by the problem they experience and their demographic background. Future research should focus on specific problems and coping strategies to gain deep domain-specific insights.